2008
DOI: 10.1128/aem.01538-07
|View full text |Cite
|
Sign up to set email alerts
|

Host-Synthesized Secondary Compounds Influence the In Vitro Interactions between Fungal Endophytes of Maize

Abstract: Maize produces a suite of allelopathic secondary metabolites, the benzoxazinoids. 2,4-Dihydroxy-7-methoxy-2H-1,4-benzoxazin-3-one and 2,4-dihydroxy-2H-1,4-benzoxazin-3-one reside as glucosides in plant tissue and spontaneously degrade to 6-methoxy-2-benzoxazolinone (MBOA) and 2-benzoxazolinone (BOA) upon plant cell disruption. Several maize-associated fungi in the genus Fusarium can metabolize MBOA and BOA. BOA tolerance levels in 10 species of Fusarium and in the maize endophytes Nigrospora oryzae, Acremonium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 47 publications
0
49
0
Order By: Relevance
“…The toxic compounds are present in a glycosylated form, while deglycosylation leads to a non-toxic metabolite. Therefore, enzymatic deglycosylation will result in tolerant microorganisms, if they have the respective enzyme (Saunders and Kohn 2008). In this study it was also observed that fungi, which can degrade the toxic conpounds, can lead the way for colonization by other, not so tolerant endophytes.…”
Section: Metabolism Of Plant Host Compounds By Endophytesmentioning
confidence: 75%
“…The toxic compounds are present in a glycosylated form, while deglycosylation leads to a non-toxic metabolite. Therefore, enzymatic deglycosylation will result in tolerant microorganisms, if they have the respective enzyme (Saunders and Kohn 2008). In this study it was also observed that fungi, which can degrade the toxic conpounds, can lead the way for colonization by other, not so tolerant endophytes.…”
Section: Metabolism Of Plant Host Compounds By Endophytesmentioning
confidence: 75%
“…While the functional roles of endophytes are understudied, they may act as defensive mutualists by conferring increased tolerance to pathogens (Arnold et al, 2003;Lee et al, 2009) or conferring competitive abilities to the host (Clay and Holah, 1999;Wilson, 1995). While effects on the host have been explored to some extent, mechanisms of interaction among plant-associated microbes have only been studied recently (Saunders and Kohn, 2008). Here, we develop methods to evaluate mechanisms and outcomes of interactions between two fungi commonly found in maize; the endophyte Fusarium verticillioides and the pathogen Ustilago maydis.…”
Section: Introductionmentioning
confidence: 98%
“…Interactions among microbes, including the endophytes, encompass antagonistic or competitive, facilitative, and apparently neutral outcomes (Mazurier et al, 2009;Saunders and Kohn, 2008;Pan and May, 2009). Interacting fungi may limit each other's growth through antibiosis, where secondary compounds limit mycelial growth, spore production or spore germination of the opposing fungi (Altomare et al, 2000;Goodman and Burpee, 1991;Nicoletti et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Abass et al [28 -30] isolated and identified these two species from heavily infected date palm leaves with leaf spot disease. In addition to date palm, several other important plants have been reported as a host for N. oryzae including rice and maize disease [32,33]. Recently, a growing number of researches proved the ability of N. oryzae to invade different plants such as kentucky bluegrass (Poa pratensis L.); sesame (Sesamum indicum L.) and wheat (Triticum aestivum L.) [34 -36].…”
Section: Discussionmentioning
confidence: 99%